Validating an Ultra-Short Survey Measure of Patience - Thomas Vischer; Thomas Dohmen; Armin Falk; David Huffman; Jürgen Schupp; Uwe Sunde; Gert G. Wagner (Economics Letters, 2013)
Abstract This study presents results of the validation of an ultra-short survey measure of patience included in the German Socio-Economic Panel (SOEP). Survey responses predict intertemporal choice behavior in incentive-compatible decisions in a representative sample of the German adult population.
Additional information: This is the author's version of a work that was accepted for publication in Economics Letters. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Economics Letters 120(2013), 2, pp. 142-145 and is online available at http://dx.doi.org/10.1016/j.econlet.2013.04.007.
Keywords: D01; D03; D91; C91; 330; Time preferences; Discounting; Validation of survey measures; Laborversuche; Individuum; Konsumentenverhalten; Mikroökonometrie; Methodenforschung